The Effectiveness Of Integrated Sensory Therapy As A Stimulation Of Speech Ability In Children Aged 2-5 Years With Functional Speech Delay Disorder - Sriadnyani, Ni Wayan; Suhita, Byba Melda; Widyowati, Agustin (Chakra Brahmanda Lentera Institute, 2024)
Background: Early childhood is a golden age and a critical period because there is a speedy growth and development process in the human life span, and it is irreplaceable in the future. Speech delay is functional. It is a delay in speaking due to lack of stimulation or the wrong parenting. One way to stimulate speech ability is through integration sensory therapy. The purpose of the study is to determine the effectiveness of integrated sensory therapy as a stimulation of speech ability in children aged 2-5 years with functional speech delay disorder at Kires Spa Dalung Methods: The design of this study is a quantitative quasi-experimental with a nonequivalent control group design. The sampling technique used was Simple Random Sampling, with a sample of 60 respondents divided into 2 groups, namely the treatment group and the control group. Data Analysis Techniques m Mann-Whitney Test. Results: The results of the study showed that of the 30 respondents in the treatment group before sensory integration therapy, the mean value (SD) of speech ability was 0.13 (0.346), and 30 respondents in the control group before the study was 0.23 (0.681). After 8 times of integrated sensory therapy on 30 respondents, the mean value (SD) of speech ability was 20.87 (0.571), and the control group after the study of the mean value (SD) of speech ability was 3.13 (0.819. The results of data analysis using the Mann-Whitney test showed a significance value of 0.000<(ɑ=0.05), meaning that H0 was rejected and H1 was accepted; this means that there is the effectiveness of sensory integration therapy as a stimulation of speech ability in children aged 2-5 years with functional speech delay disorder. Conclusion: Integrated sensory therapy is very effective in helping improve speech skills in children with functional speech delays. Future research should explore the long-term effects of integrated sensory therapy on speech development in children with functional speech delays across diverse populations and age groups.